Improvement of medical judgments by numerical training in patients with multiple sclerosis. (5th September 2018) - Zamarian, L.; Delazer, M.; Ehling, R.; Pertl, M.‐T.; Bsteh, G.; Wenter, J.; Glatzl, S.; Brenneis, C.; Benke, T.; Berger, T.
Abstract : Background and purpose: People with multiple sclerosis (MS) have to face important decisions with regard to their medical treatment. The aim of this study was to evaluate whether a targeted cognitive training reduces framing effects and thus improves medical judgments. Methods: This was a randomized, double‐blind, cross‐over study enrolling patients with relapsing‐remitting MS and healthy controls (HCs). Participants were randomly assigned to training order A (first week, numerical training; second week, control training) or B (reverse order). The primary endpoint was changed in a framing task score (framing effect). In the framing task, participants evaluated the success of fictive medications on a 7‐point scale. Medications were described in either positive or negative terms. Results: A total of 37 patients and 73 HCs performed either training order A ( n = 56) or B ( n = 54). The framing effect decreased after the numerical training regardless of training order. No such decrease was found after the control training. Mean change in framing effect was −0.3 ± 0.8 after the numerical training and 0.03 ± 0.6 after the control training. This specific effect of training type was comparable between groups. Conclusion: Judgments of medical information improve in both patients with relapsing‐remitting MS and HCs after a targeted numerical training. Thus, a specific cognitive intervention may help patients making informed decisions.